2021
DOI: 10.1111/jan.14954
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of interventions targeting fundamental care to reduce hospital‐associated decline in older patients

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…There is evidence that multicomponent interventions addressing fundamental principles of age-friendly care, including mobility, cognitive and social activities, nutrition and hydration, sleep, and pain management, significantly reduce the incidence of delirium 8 and may reduce the incidence of falls 9 and hospital-associated disability, 10 suggesting that systematic attention to these fundamental principles could have an additive effect on HAC-OPs and mediate better outcomes for older people. 11,12 However, these principles remain challenging to implement within complex health services. 13,14 "Eat Walk Engage" is a ward-based improvement program designed to support more consistent delivery of the key principles of nutrition and hydration, mobility, and meaningful cognitive and social engagement, as well as improve multidisciplinary teamwork.…”
mentioning
confidence: 99%
“…There is evidence that multicomponent interventions addressing fundamental principles of age-friendly care, including mobility, cognitive and social activities, nutrition and hydration, sleep, and pain management, significantly reduce the incidence of delirium 8 and may reduce the incidence of falls 9 and hospital-associated disability, 10 suggesting that systematic attention to these fundamental principles could have an additive effect on HAC-OPs and mediate better outcomes for older people. 11,12 However, these principles remain challenging to implement within complex health services. 13,14 "Eat Walk Engage" is a ward-based improvement program designed to support more consistent delivery of the key principles of nutrition and hydration, mobility, and meaningful cognitive and social engagement, as well as improve multidisciplinary teamwork.…”
mentioning
confidence: 99%
“…Of these, 12 were excluded for failing to meet the inclusion criteria or the objective of the umbrella review. Fourteen reviews met the inclusion criteria [ 31 , 32 , 34 , 35 , 41 , 42 , 43 , 44 , 45 , 46 , 53 , 54 ]. The results are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Richards et al reviewed nurse‐led interventions to address FoC and concluded that evidence remained sparse and of insufficient quality to provide guidance to nursing practice (Richards et al, 2018). In contrast, de Foubert et al took a broader view and included interventions involving ward nurses which were led by any health professional and found promising evidence for improving both processes and outcomes of FoC for older people (de Foubert et al, 2021). They highlighted the value of multi‐component approaches, recognizing the importance of integration across domains, and recommended the explicit use of knowledge translation frameworks to guide improvement, acknowledging the powerful influence of local and wider contextual factors on nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity, frailty and hospital care processes interact to increase the risk of hospital‐associated complications in older people including delirium, functional decline, incontinence, falls and pressure injuries, which affect almost half of hospitalized older people (Bail & Grealish, 2016; Hubbard et al, 2017; Mudge et al, 2019; Zisberg et al, 2015). These risks can be mitigated by the consistent provision of high‐quality fundamentals of care (FoC) such as adequate nutrition and hydration; support for physical, cognitive and social activities to maintain and recover function; and adequate sleep and pain relief (Burton et al, 2021; de Foubert et al, 2021). In this discussion paper, we argue that leadership approaches to reliable provision of FoC must embrace complexity, both of older patients' needs and the complex setting in which nurses and other health care staff work, through multidisciplinary partnerships, application of knowledge translation tools appropriate for complex interventions and enabling emergent leadership at every level.…”
Section: Introductionmentioning
confidence: 99%